2010
DOI: 10.1007/s00394-010-0136-5
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption but not green tea consumption is associated with adiponectin levels in Japanese males

Abstract: We not only revealed that habitual coffee consumption is associated with higher adiponectin levels in Japanese males but also found a dose-dependent association between coffee consumption and adiponectin levels. Therefore, our study suggested that coffee components might play an important role in the elevation of adiponectin level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 31 publications
3
31
0
3
Order By: Relevance
“…In a clinical trial study, a significant increase in adiponectin levels in response to increasing coffee consumption was found among participants with an elevated risk for type 2 diabetes [32]. The favorable association between moderate coffee consumption and adiponectin levels in the present study is consistent with other recent cross-sectional studies [31,33]. It is possible that coffee could alter adiponectin synthesis or secretion in response to visceral fat accumulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a clinical trial study, a significant increase in adiponectin levels in response to increasing coffee consumption was found among participants with an elevated risk for type 2 diabetes [32]. The favorable association between moderate coffee consumption and adiponectin levels in the present study is consistent with other recent cross-sectional studies [31,33]. It is possible that coffee could alter adiponectin synthesis or secretion in response to visceral fat accumulation.…”
Section: Discussionsupporting
confidence: 92%
“…However, only a relatively small number of studies have investigated the relationships between coffee consumption and adiponectin. A prospective cohort study in the United States showed that women with or without diabetes who drank at least four cups of coffee per day showed significantly higher adiponectin levels than those who did not drink coffee on a regular basis [21], and dose-response relationships were found in Japanese men [31]. In a clinical trial study, a significant increase in adiponectin levels in response to increasing coffee consumption was found among participants with an elevated risk for type 2 diabetes [32].…”
Section: Discussionmentioning
confidence: 97%
“…Several prospective epidemiological studies report a negative correlation between caffeine consumption and risk of various cancers in humans [2,3]. In order to experimentally represent the etiology of tumor initiation, 3-MCA, a complete carcinogen that mediates both initiation and promotion of tumor development, was used in the present study [29].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, meta-analysis studies comprised of >800,000 subjects revealed that caffeine consumption is associated with significantly decreased risk for cutaneous malignant melanoma [1], liver cancer [2,3] and pancreatic cancer [4]. Coffee is a leading source of methylxanthines, such as caffeine (1,3,7-trimethylxanthine), and while the immunomodulatory properties of many of the methylxanthines have been widely investigated, very few studies have directly examined the effects of caffeine on anti-tumor immune cell functions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Results on adiponectin levels and green tea intake are available in one short-term clinical study [58] and two cross-sectional studies [59, 60]. In a randomized controlled trial of obese men and women with metabolic syndrome, there were no significant differences in adiponectin levels between subjects randomized to green tea beverage (440 mg EGCG) (n=11) or green tea extract (460 mg EGCG) (n=7) compared to those randomized to no green tea treatment (n=11) [58].…”
Section: Green Tea and Biomarkers Of Breast Cancer Riskmentioning
confidence: 99%